Summation of Temporal L-Cone- and M-Cone-Contrast in the Magno- and Parvocellular Retino-Geniculate Systems in Glaucoma - Huchzermeyer, Cord; Horn, Folkert; Lämmer, Robert; Mardin, Christian; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2021)
Purpose: The purpose of this study was to characterize summation of temporal L- and M-cone contrasts in the parvo- (P-) and magnocellular (M-) pathways in glaucoma and the relationship between the respective temporal contrast sensitivities (tCS) and clinical parameters. Methods: Perifoveal tCS to isolated or combined L- and M-cone contrasts (with different contrast ratios, and therefore different luminance and chromatic components) were measured at different temporal frequencies (at 1 or 2 Hz and at 20 Hz) using triple silent substitution in 73 subjects (13 healthy, 25 with glaucoma, and 35 with perimetric glaucoma). A vector summation model was used to analyze whether perception was driven by the P-pathway, the M-pathway, or both. Using this model, L- and M-cone input strengths (AL, AM) and phase differences between L- and M-cone inputs were estimated. Results: Perception was always mediated by the P-pathway at low frequencies, as indicated by a median phase angle of 179.84 degrees (cone opponency) and a median AL/AM ratio of 1.04 (balanced L- and M-cone input strengths). In contrast, perception was exclusively mediated by the M-pathway at higher frequencies (input strength not balanced: AL/AM = 2.94, median phase angles = 130.17 degrees). Differences in phase were not significant between diagnosis groups (Kruskal-Wallis = 0.092 for P- and 0.35 for M-pathway). We found differences between groups only for the M-pathway (L-cone tCS deviations at 20 Hz were significantly lower in the patients with glaucoma P = 0.014, with a strong tendency in M-cones P = 0.049). L-cone driven tCS deviations at 20 Hz were linearly correlated with perimetric mean defect (MD) and quadratically correlated with retinal nerve fiber layer (RNFL) thickness. Conclusions: Unaltered phase angles between L- and M-cone inputs in glaucoma indicated intact temporal processing. Only in the M-pathway, contrast sensitivity deviations were closely related to diagnosis group, MD, and RNFL thickness, indicating M-pathway involvement.
CRIS-Team Scopus Importer:2021-06-04